Winning basketball fundamentals - Rose, Lee H (Human Kinetics, 2013)
Lee Rose has developed hundreds of players at the high school, collegiate, and professional levels throughout his 50-year coaching career. He shares his knowledge of the game in Winning Basketball Fundamentals with offensive and defensive strategies, individual and team drills, and a valuable player evaluation system to help guide coaching efforts.